2020
DOI: 10.5217/ir.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated promoters of tumor suppressor genes were identified in Crohn’s disease patients

Abstract: Background/Aims: Overwhelming evidence suggests that inflammatory bowel disease (IBD) is caused by a complicated interplay between the multiple genes and abnormal epigenetic regulation in response to environmental factors. It is becoming apparent that epigenetic factors are significantly associated with the development of the disease. DNA methylation remains the most studied epigenetic modification, and hypermethylation of gene promoters is associated with gene silencing.Methods: DNA methylation alterations ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In addition, the hypermethylated TFPI2 was also found in patients with Crohn disease. 44 These results imply the potential risk of more falsepositive detections when combining TFPI2 and SDC2.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the hypermethylated TFPI2 was also found in patients with Crohn disease. 44 These results imply the potential risk of more falsepositive detections when combining TFPI2 and SDC2.…”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, our results showed that SFRP5 inhibits melanin synthesis in melanocytes through the Wnt/β-catenin signaling pathway in vitro and exhibits melanin-inhibiting activity in vivo . As for the possible mechanism of SFRP5 upregulation in vitiligo melanocytes and vitiligo skin lesions, we speculate that it may be regulated by epigenetics, 74 inflammation, 75 and immune-mediated factors. 76 In recent years, epigenetic changes in SFPR5, such as SFRP5 gene methylation have been closely related to the occurrence and development of various tumors.…”
Section: Discussionmentioning
confidence: 98%
“…47 One Korean study identified hypermethylated promoters of tumor suppressor genes (TSGs) in patients with CD, suggesting they may be candidate noninvasive diagnostic markers of IBD. 48…”
Section: Disease Susceptibility Genes and Diagnostic Biomarkers For Ibdmentioning
confidence: 99%